Characteristics and Outcomes of Patients With Takotsubo Syndrome: Incremental Prognostic Value of Baseline Left Ventricular Systolic Function. Issue 16 (18th August 2020) - Alashi, Alaa; Isaza, Nicolas; Faulx, Jackson; Popovic, Zoran B.; Menon, Venu; Ellis, Stephen G.; Faulx, Michael; Kapadia, Samir R.; Griffin, Brian P.; Desai, Milind Y.
Abstract : Background: We sought to determine (1) long‐term outcomes in patients presenting with documented Takotsubo syndrome (TS), (2) whether left ventricular global longitudinal strain (LV‐GLS) provides incremental prognostic value, and (3) prognostic cutoffs of LV ejection fraction (LVEF) and LV‐GLS during an acute TS episode. Methods and Results: We studied 650 patients with TS (aged 66±14 years, 88% women) who were diagnosed clinically and angiographically between 2006 and 2018. Baseline LVEF and LV‐GLS (using velocity vector imaging) were recorded. The primary end point was all‐cause mortality. TS triggers were unknown (34%), emotional (16%), physical (41%), and neurologic (10%). Mean LVEF and LV‐GLS were 36±10% and −11.6±0.4%; in addition, 94% patients had LVEF <52%, and 80% had apical ballooning. No patient had obstructive coronary artery disease. At a median of 2.2 years (interquartile range, 0.7–4.4), 175 (27%) had died (9% in‐hospital deaths). Multivariate Cox survival analysis revealed that higher age (hazard ratio [HR], 1.35), male sex (HR, 1.75), lower baseline LVEF (HR, 1.02), worse LV‐GLS (HR, 1.04), neurologic trigger (HR, 2.66), and physical trigger (HR, 2.64) were associated with mortality, whereas aspirin (HR, 0.70) and β‐blockers (HR, 0.73) improved survival (all P <0.049). The addition of LVEF and LV‐GLS to clinical markers (age, sex, cardiogenic shock at presentation, and peak troponin I) significantly increased log‐likelihood ratios: clinical (−521.48), clinical plus LVEF (−511.32, P <0.001), and clinical plus LVEF and LV‐GLS (−500.68, P <0.001). On penalized spline analysis, LVEF of 38% and LV‐GLS of −10% were cutoffs below which survival was significantly worse. Conclusions: Patients with TS with a neurologic or physical trigger had significantly worse survival than those without such a trigger, with baseline LVEF and LV‐GLS providing incremental prognostic value.